The Effect of Conflict Management and Employee Training on the Work Ability of Coffeeshop Baristas in Padang City - Habby Burahman; Gesit Thabrani (Human Resource Management Studies, 2022)
This study aims to determine the effect of conflict management and employee training on the work ability of coffeeshop baristas in Padang City. This study uses descriptive statistical data analysis techniques and multiple linear regression test with quantitative methods. The population in this study were baristas from the brewtherhood forum in Padang City with a sample of 40 respondents. In this study, the data collection technique was using a questionnaire. Based on the results of this study it shows that conflict management has a significant and positive effect on work ability which can be proven by the value of t count > t table that is 2.299 > 2.026, employee training has a significant and positive effect on work ability with t count 2.173 > t table 2.026. In addition, the two independent variables of conflict management and employee training have a significant and simultaneous effect on work ability where the value of Fcount is 25,449 > Ftable 3,24.